Application of Problem Based Learning Method to Improve Communication Competence Course - Rahmanto, Andre (Sebelas Maret University, 2016)
Conflict Management is one of the basic competences in Communication Science subjects in the studyprogram in educational administration office (PAP) FKIP UNS. Communication is needed to handleconflict appropriately, so as not to damage the relationship between personal and organizational goals.This is a classroom action research (CAR) with two cycles carried out by researchers as lecturer.Methods of Problem-Based Learning (PBL) assisted with the setting of film Media Company /organization in studying the problem, the reality of the world is expected to organizations that have notbeen experienced by participants and can be brought closer to the concepts they are learning. Theresearch was conducted at the Communication Class in FKIP UNS at semester 3 from June to October2011. Data collection techniques used in this study are: observation, interviews, tests andquestionnaires. Data analysis was performed by using comparative descriptive and critical analysistechniques. The results showed the use of PBL method in managing material conflicts shows that themethod is successful in increasing the competence of students from the class average 70.33 in the firstcycle to 78.27 in the second cycle (improved for 11.28%). Student response to the PBL method waspleased to learn (80%); encouraged to think and express opinions (79%), better understand the conceptand are not quickly forgotten (78%) and innovative (77%).